Sarana Dan Prasana Perspektif Al Quran dan Hadis (Pendekatan Al-Quran Dan Hadits Tematik) - Abd Ghafur (LP3M UNZAH GENGGONG, 2021)
Abstract This scientific work aims to examine the contextual values ​​of the management of facilities and infrastructure from the perspective of Al-Hadith and the Qur'an in terms of the components of planning, utilization, inventory, and supervision of facilities and infrastructure. The type of method used is the maudhu'i (thematic) interpretation method which collects verses of the Qur'an that have one goal together to discuss certain titles/topics/sectors and discipline them wherever possible according to the period of decline in harmony with the cause. - because of the decline. The first result, the context of the management of facilities and infrastructure in the interpretation of newspapers is contained in the interpretation of An-Nahl (16) verses 68-69, namely mapping the concept of building the division of labor in compiling infrastructure to be effective and on target so that its implementation is in accordance with its value. Second, planning the interpretation of al-Hasyr (59) verse 18 for each individual to design their future preparations so that what will be done has been formulated as a conception of the realization of activities. Third, the use of An-Nahl's interpretation (16) paragraphs 5-8 is so that every human being can maximize every potential resource that exists, both human resources and natural resources as effectively and efficiently as possible so that the potential that exists in these resources can be maximized. Fourth, the inventory of interpretations of the letter Al-Baqarah (2) paragraph 282 regarding the urgency of recording as concrete, factual and authentic evidence in reporting so that it can be easier to check and become textual data when there is accountability from school institutions. Fifth, supervision of the interpretation of Al-Mujaadillah (58) paragraph 7 surah is absolute to avoid deviations in terms of reporting, performance and output. Keywords: Management, Facilities, Qur'an and Hadith